Nocturnal respiratory rate as a predictor of mortality in patients with acute coronary syndrome. Issue 2 (5th November 2018) - Eick, Christian; Groga-Bada, Patrick; Reinhardt, Kathrin; Duckheim, Martin; Mizera, Lars; Böhm, Katharina; Götz, Nina; Gawaz, Meinrad; Zürn, Christine
Abstract : Background: Patients with acute coronary syndrome (ACS) are at risk especially in the period shortly after the event. Alterations in respiratory control have been associated with adverse prognosis. The aim of our study was to assess if the nocturnal respiratory rate (NRR) is a predictor of mortality in patients with ACS presenting in the emergency department. Methods: Clinically stable consecutive patients with ACS aged ≥ 18 years were prospectively enrolled. The Global Registry of Acute Coronary Events (GRACE) score and left ventricular ejection fraction (LVEF) were assessed for all patients. The average NRR over a period of 6  hours was determined by the records of the surveillance monitors in the first night after admission. Primary and secondary endpoints were intrahospital and 2  years all-cause mortality, respectively. Results: Of the 860 patients with ACS, 21 (2.4%) died within the intrahospital phase and 108 patients (12.6%) died within the subsequent 2 years. The NRR was a significant predictor of both endpoints and was independent from the GRACE score and LVEF. Implementing the NRR into the GRACE risk model leads to a significant increase of the C-statistics especially for prediction of intrahospital mortality. Conclusion: The NRR is an independent predictor of mortality in patients with ACS.